Self-Security and its Relation to Decision Making in Teachers at the College of Education for Humanities - Ghanim Ali, Saad; Qadr Mahmood, Amosh Abdul (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The objective of this research is to identify the relationship between personal security and decision making among the teaching staff of the Faculty of Education of Human Sciences in light of the variables: displacement, sex and marriage. The research sample consisted of 54 teachers who were displaced outside the city of Mosul during their occupation: Those who remained in the city for the academic years 2014 - 2017, and those who did not move. The results were analyzed using the Pearson correlation coefficient and its T value.